SIGNS OF SILVER-BEARING CAPACITY OF VOLCANIC STRUCTURES IN THE OKHOTSK-CHUKCHI BELT - Kolesnikov D.I.; Rozinov M.I.; Shatkov N.G. (My University, 2001)
Potential mineralization of volcanic structures is determined by geochemical potential of composing rhyolites, i.e. by original silver (and gold) content in unaltered rocks. It is realized due to metasomatic transformations of rocks. The scale of ore-forming processes development depends on the volumes of transforming rocks and is conditioned by peculiarities of the volcanic structures tectonic evolution. As exemplified by a unique Dukat deposit, a positive role of the following factors has been established: superposition of heat impulses with moderate intensity that do not cause rock metamorphism, involvement of volcanic rocks into uplifting and cracking, structural-lithological barriers that restrict lateral spreading and vertical movement of the geothermal system.